Side effects following first dose of COVID-19 vaccination in Ho Chi Minh City, Vietnam - Si Van Nguyen; Bay Thi Nguyen; Huong Nguyen Viet Duong; Phong Thanh Lenh; Kien Trung Tran; Hoa Minh Tran; Thanh Cong Nguyen; Dung Phuong Nguyen; My Ngoc Ta; Nhut Nguyen Minh Trieu; Nam Ba Nguyen; Hung Quang Tran; et al. (Taylor & Francis Group, 2023)
Vaccines are strongly recommended globally as an effective measure to prevent serious illness from and spread of COVID-19. Concerns about safety following vaccination continue to be the most common reason that people do not accept the vaccine. This retrospective study was carried out on 4341 people who received the first dose of ChAdOx1 nCoV-19, BBIBP-CorV, or mRNA-1273 vaccine at Jio Health Clinic in Ho Chi Minh City, Vietnam. Post-injection side effects were either reported by participants or actively collected by health care staff by means of telemedicine. Local side effects were reported by 35.5% of all individuals, with pain being the most common symptom (33.3%). Systemic side effects were reported by 44.2% of individuals, with fever (25.3%) and fatigue (21.4%) being the most common. Age ≤60 years, female gender, and ChAdOx1 nCoV-19 were significant independent risk factors for both local and systemic side effects, while a history of allergy was significant as a risk factor for local side effects. A total of 43 individuals (1.0%) reported concerning symptoms of rare severe complications, which were addressed and treated by physicians via Jio Health app.